Avrupa Birliği Enerji Politikaları ve Enerji Arz Güvenliği Arayışları (European Union Energy Policy and Seeking for Security of Energy Supply) - Furkan Yıldız (İnsan & Toplum)
The usage of energy is as old as humanity itself. From past to present, humans has used energy to sat isfy their most basic needs like providing themselves heat and for nutrition. Thereafter, energy started to be used for industrial activities. With the transition in the production process after the Industrial Revolution, energy became one of the most strategic requirements for nations. The foundation of the European Coal and Steel Community (ECSC) in 1951 and the establishment of the European Atomic Energy Community (Euratom) stemming from the Treaty of Rome in 1957, and the European Economic Community (EEC) laid the foundations of the European Union (EU). Two thirds of the organizations which founded the EU have focused onenergy which shows the importance of issues related to energy sharing in the establishment of the Union. In this article, EU energy policies are discussed within the context of energy supply security, focusing firstly on how the general lines of the EU’s energy profile will unfold along with their strengths and weaknesses. It will then continue by discussing the historical process energy policies of the Union will be determined. In the following section, this article will attempt to ascertain the degree of energy supply security in the EU as well as examine the policies of the Union within the context of increasing security in energy supply.